2014
DOI: 10.1074/jbc.m113.538223
|View full text |Cite
|
Sign up to set email alerts
|

Global Ablation of the Mouse Rab11a Gene Impairs Early Embryogenesis and Matrix Metalloproteinase Secretion

Abstract: Background:The physiological role of Rab11a in mouse embryogenesis has not been fully studied. Results: Using a Rab11a null mouse allele, the transport of multiple membrane-associated and soluble cargos was analyzed in mouse blastocysts and MEFs. Conclusion: Rab11a ablation impairs mouse blastocyst development and the secretion of soluble matrix metalloproteinases. Significance: In vivo functions of Rab11a in mouse fetal development and soluble MMP secretion were uncovered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
47
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 41 publications
(54 citation statements)
references
References 77 publications
5
47
0
Order By: Relevance
“…Blastocyst hatching in vitro is brought about by increasing pressure from the expanding blastocyst combined with zona-thinning embryo-secreted proteases, where implantation serine protease 1 (ISP1, also known as strypsin) is thought to play a vital role (Ichikawa et al, 1985;O'Sullivan et al, 2001;Perona and Wassarman, 1986;Sawada et al, 1990;Sharma et al, 2006). An increase in hatching rate may be due to an overall improvement in embryo health, but during culture proteases are secreted into the culture media (Hwang et al, 2000;Martinez-Hernandez et al, 2011;Sawada et al, 1990;Whiteside et al, 2001;Yu et al, 2014), and could assist in the zona degradation and hatching of neighbouring embryos. Also, it has been suggested that protease production for hatching may be stimulated by growth factors and cytokines (Seshagiri et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Blastocyst hatching in vitro is brought about by increasing pressure from the expanding blastocyst combined with zona-thinning embryo-secreted proteases, where implantation serine protease 1 (ISP1, also known as strypsin) is thought to play a vital role (Ichikawa et al, 1985;O'Sullivan et al, 2001;Perona and Wassarman, 1986;Sawada et al, 1990;Sharma et al, 2006). An increase in hatching rate may be due to an overall improvement in embryo health, but during culture proteases are secreted into the culture media (Hwang et al, 2000;Martinez-Hernandez et al, 2011;Sawada et al, 1990;Whiteside et al, 2001;Yu et al, 2014), and could assist in the zona degradation and hatching of neighbouring embryos. Also, it has been suggested that protease production for hatching may be stimulated by growth factors and cytokines (Seshagiri et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, Rab8a KO mice also show deficits in microvillus formations in the intestines and these defects are augmented in Rab8a/Rab8b double KO mice [38,39 • ]. While Rab11a germline KO mice are embryonic lethal [40], targeted KO of Rab11a in intestinal enterocytes leads to short apical microvilli and deficits in TLR9 recycling [4143]. …”
Section: Components Of the Apical Recycling System Influence The Mainmentioning
confidence: 99%
“…The conditional Rab11a floxed allele mice were derived from homologous recombination in embryonic stem cells as described previously by Yu, et al (Yu et al, 2014a;Yu et al, 2014b). The Rab8a-knockout mice used for the study have also been described previously by Sakamori et al (Sakamori et al, 2012;Sato et al, 2007).…”
Section: Micementioning
confidence: 99%